Rett Syndrome - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1992)
The late infantile regression period (stages I and II) was analyzed retrospectively in 91 girls and women at the Department of Pediatrics, University of Goteborg and Pediatric Clinic, Ostersund Hospital, Sweden.